Anti-Obesity And Anti-Hyperlipidemic Activity Of Terminalia Catappa Linn. In High-Fat-Diet Induced Obese Rats - Mukundan, Usha; Sharma, Ambikadevi (Asian Journal of Pharmaceutical Research and Development, 2013)
Obesity is recognized as a social problem, associated with serious health risks and increased mortality. The incidence of obesity has increased at an alarming rate in recent years, becoming a worldwide health problem with incalculable social costs. Numerous trials have been conducted to find and develop new anti-obesity drugs through herbal sources to minimize side effects associated with the present anti-obesity drugs in the market. The present study was designed to evaluate the anti-obesity and anti-hyperlipidemic activity of leaves of Terminalia catappa Linn. Preliminary phytochemical screening has also been performed on the powdered leaf. Phytochemical analysis indicated presence of alkaloids, tannins, saponins and flavonoids in methanolic leaf extract of Terminalia catappa Linn. The oral administration of methanolic leaf extract of Terminalia catappa Linn. at high dose of 400 mg/kg body weight resulted in decrease total cholesterol, triglycerides, LDL in high fat diet treated obese animals. The results showed that treatment with Atorvastatin a standard anti obesity drug reduced the triglycerides of HFD fed obese rats by 19% while 200 mg/kg and 400 mg/kg body weight of methanol leaf extract of Terminalia catappa Linn. caused a reduction of 9% and 17% respectively in the high fat diet treated animals. Atorvastatin reduced body weight of high fat diet fed obese rats by 16% while 200 mg/kg and 400 mg/kg body weight of methanol leaf extract of Terminalia catappa caused a reduction of 8% and 11% respectively in body weight during the treatment period.